HIROIMONO is NP-complete - Andersson, Daniel (BRICS Report Series, 2007)
In a Hiroimono puzzle, one must collect a set of stones from a square grid, moving along grid lines, picking up stones as one encounters them, and changing direction only when one picks up a stone. We show that deciding the solvability of such puzzles is NP-complete.